2008
DOI: 10.1590/s1516-31802008000500002
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of quality of life among patients on dialysis in southern Brazil

Abstract: CONTEXT AND OBJECTIVE: Quality of life (QoL) is considered important as an outcome measurement, especially for long-term diseases such as chronic renal failure. The present study searched for predictors of QoL in a sample of patients undergoing dialysis in southern Brazil. DESIGN AND SETTING:This was a cross-sectional study developed in three southern Brazilian dialysis facilities.METHODS: Health-related QoL of patients on hemodialysis or peritoneal dialysis was measured using the generic Short Form-36 (SF-36)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
7
16

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 15 publications
6
29
7
16
Order By: Relevance
“…This finding is in line with several studies that showed similar results (21)(22)(23)(24). The negative effect of the disease process on the physical activity of patients, such as a decrease in haematocrit, and musculoskeletal and neurological problems may contribute to this finding.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in line with several studies that showed similar results (21)(22)(23)(24). The negative effect of the disease process on the physical activity of patients, such as a decrease in haematocrit, and musculoskeletal and neurological problems may contribute to this finding.…”
Section: Discussionsupporting
confidence: 91%
“…O tratamento da DRC por meio de diálise melhora o tempo de sobrevida dos pacientes, entretanto, a natureza progressiva da doença gera um desequilí-brio ou disfunção a longo prazo. A utilização exacerbada de medicamentos e a dependência de uma má-quina contribuem para debilitar o doente renal e comprometer suas atividades de vida diária, 23 reduzindo sua capacidade aeróbica. 24 Esses comprometimentos estão relacionados às inúmeras alterações sistêmicas, físicas e fisiológicas forçado no primeiro segundo (VEF1) e o Índice Tiffeneau (VEF1/CVF) muito abaixo do previsto, em 30 pacientes portadores de DRC submetidos à hemodiálise.…”
Section: Tabelaunclassified
“…The physical domain of the WHOQOL-Bref has seven facets: pain and discomfort, energy and fatigue, able to get around, sleep and rest, activities of daily living, dependence on medications or treatments and capacity for work (4) . In our sample, the mean scores of the physical domain ranged from 9.94 (SD 1.78) before kidney transplantation to 17.41 (SD 1.78) after kidney transplantation.…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that the renal graft survival time is associated with the monitoring of patient by specialized professionals and treatment adherence (1,4) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation